2007
DOI: 10.1089/apc.2006.0219
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Stigma in Health Care Settings: A Survey of Service Providers in China

Abstract: We examined how individual and institutional factors in health care settings affected discrimination toward persons with HIV/AIDS. A representative sample of 1101 Chinese service providers was recruited in 2005, including doctors, nurses, and laboratory technicians. Multiple regression models were used to describe associations among identified variables, the relationships with HIV-related personal prejudicial attitudes, and perceived institutional support and discrimination at work. Multivariate analyses revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
146
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(168 citation statements)
references
References 33 publications
16
146
3
3
Order By: Relevance
“…[10][11][12][13] One such setting is health care. 14,15 Previous research has documented stigmatizing beliefs and attitudes on the part of health care providers [16][17][18][19] and a lack of willingness to interact with, or care for, PLWH in hypothetical situations. 18,[20][21][22] Additionally, actual discriminatory practices have been documented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] One such setting is health care. 14,15 Previous research has documented stigmatizing beliefs and attitudes on the part of health care providers [16][17][18][19] and a lack of willingness to interact with, or care for, PLWH in hypothetical situations. 18,[20][21][22] Additionally, actual discriminatory practices have been documented.…”
mentioning
confidence: 99%
“…14,15 Previous research has documented stigmatizing beliefs and attitudes on the part of health care providers [16][17][18][19] and a lack of willingness to interact with, or care for, PLWH in hypothetical situations. 18,[20][21][22] Additionally, actual discriminatory practices have been documented. These range from subtle to blatant and include awkward social interactions, increased physical distance, avoidance, unnecessary referrals to other health care providers, neglect, the discouragement of treatment regimens, contempt, testing without consent, blaming, excessive protective measures, the labeling of charts, beds, and/or rooms, breaches of confidentiality, refusal to treat, isolation in wards, and verbal abuse.…”
mentioning
confidence: 99%
“…In terms of age, majority 46.% fall between age range of 34-41yrs while only about 7.2% fall within 26-33yrs, 67.2% of the respondents were married while only 9.6% were single, 45.2% of them were graduate of various tertiary institution while only 4.4% did not have any formal education. Majority of the respondents 37.2% were self-employed while only 4.4% were casual workers, 16% were unemployed due to unavailability of job(30%), poor health (27.5%) while 10% were dismissed due to poor health (17,18,19,20) . In terms of the source of knowledge, Newspapers/magazines were the major source of information about HIV/AIDS (56%), 29.6% on radio and 12% on television (20).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…About 45% of the respondents have been denied admission into the hospital, majority of them (42.9%) indicted Nurses of being the brain behind the denied, 34.4% of the respondents were not happy and viewed the practice as discriminatory for their status to conspicuously written on their case files, 33.6% noticed separation from other patients as discriminatory in nature while others viewed frequent change of protective wears and gloves more than with others patients as a way of discrimination against PLWHA (17,14,20) . Also, fear of discrimination accounted for 54.8% of PLWHA not accessing health facility, 25.2% of them believed health care personal will not help while only 4.4% could not access health facility due to lack of financial means 52.8% of the respondents were of the opinion that health workers discriminated because of their belief PLWHA are indecent and deserve to be punished, 19.2% fear being infected while 13.6% due to lack of adequate materials to practice safe medicine.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…20 Indeed, stigma among healthcare providers has been found to be a barrier to care for multiple vulnerable populations, including people living with HIV (PLWH), people who inject drugs (PWIDs), and men who have sex with men (MSM). [21][22][23] A study on healthcare providers in Malaysia found that physicians' decisions to defer antiretroviral therapy for HIV patients may be due, in part, to prejudice toward these patients. 24 Transgender people may need to access medical care for general and transition-related healthcare needs, including hormone therapy or gender-affirming surgeries.…”
Section: Discrimination From Healthcare Providers and Transgender Healthmentioning
confidence: 99%